The correlation between selenium intake and lung function in asthmatic people: a cross-sectional study - Jiang, Hejun; Yang, Guijun; Chen, Jing; Yuan, Shuhua; Wu, Jinhong; Zhang, Jing; Zhang, Lei; Yuan, Jiajun; Lin, Jilei; Chen, Jiande; Yin, Yong (Frontiers in Nutrition, 2024)
Abstract Objective: This study aimed to examine the correlation between selenium intake and lung function in asthmatic people. Methods: A total of 4541 individuals in the US National Health and Nutrition Examination Survey (NHANES) were included in this study. Multivariate linear regression, variance inflation factor, restricted cubic splines and quantile regression were used to analyze the relationship between Se intake and lung function. We divided selenium intake into four levels based on quartiles: Q1: Se ≤ 76.75 mcg/d; Q2: 76.75-105.1 mcg/d; Q3: 105.1–137.65 mcg/d; and Q4: Se ≥137.65 mcg/d. Results: Asthma was negatively associated with The Ratio of Forced Expiratory Volume 1st Second to Forced Vital Capacity (FEV1/FVC) (β = -0.04, 95% CI: -0.06 to -0.02) and FEV1 (β = -215, 95% CI: -340 to -90). Se intake was positively associated with Forced Expiratory Volume 1st Second (FEV1) (β =3.30 95% CI: 2.60 to 4.00) and Forced Vital Capacity (FVC) (β =4.30, 95% CI: 3.50 to 5.10). In asthmatic individuals, the positive effects of Se intake on FVC were enhanced with increasing Se intake, while the positive effects of Se intake on FEV1 varied less dramatically. High Se intake (Q4 level, above 137.65 mcg/d) improved FVC (β= 353, 95% CI: 80 to 626) and FEV1 (β= 543, 95% CI: 118 to 969) in asthmatic patients compared to low Se intake (Q1 level, below 76.75 mcg/d). At the Q2 level (76.75-105.1 mcg/d)) and Q4 level (Se ≥137.65 mcg/d) of Se intake, the correlation between FEV1 and asthma disappeared. Conclusions: Our research has revealed a positive correlation between selenium intake and lung function in asthma patients and the strength of this positive correlation is related to the amount of selenium intake. We recommend that asthma patients consume 137.65 mcg to 200 mcg of selenium daily to improve pulmonary function while avoiding the adverse effects of selenium on the human body.